Reliability and validity of the Caregiver Reported Early Development Instruments (CREDI) in impoverished regions of China - Ying Li; Lei Tang; Yu Bai; Shuhang Zhao; Yaojiang Shi (BMC, 2020)
Abstract Background There is a great need in low- and middle- income countries for sound qualitative and monitoring tools assessing early childhood development outcomes. Although there are many instruments to measure the developmental status of infants and toddlers, their use in large scale studies is still limited because of high costs in both time and money. The Caregiver Reported Early Development Instruments (CREDI), however, were designed to serve as a population-level measure of early childhood development for children from birth to age three, and have been used in 17 low- and middle-income countries. This study aimed to examine the reliability and validity of the CREDI in China, which is still unknown. Methods The CREDI and the ASQ-3 was administered to a sample of 946 children aged 5-36 months from urban and rural communities, in which 248 children was administered with Bayley-III. Results The internal consistency of the CREDI was high, which indicates that the scale internal consistency reliability is quite good. The results also indicated that the concurrent validity of the CREDI with the Bayley-III scale was high in general. Ordinary least squares regression showed that the CREDI is highly consistent with previous widely used instruments in some key predictors (such as the home stimulation) of early childhood development level. Conclusions All the results in the current study indicate that the CREDI may be considered an appropriate instrument to measure early childhood development status on a large scale in impoverished regions of China.